Effect of Coronavirus-19 on Mental Condition of International Students in China - Manzoor, Faiza; Wei, Longbao; Haq, Muhammad Zia ul (Frontiers in Psychiatry, 2022)
Despite its importance, no study investigates the effects of coronavirus-19 on the mental condition of international students in China. By using data from international students in China, this study finds the positive and affirmative connection between fear of coronavirus-19 and generalized anxiety disorder among foreign students. Furthermore, this study reveals a negative association between coronavirus-19 fear and the psychological well-being of foreign students in China. We also find that emotional intelligence has a positive and optimistic moderating influence on the relationship between fear of coronavirus-19 and generalized anxiety disorder but it has not moderating effect on the relationship between fear of coronavirus-19 and psychological well-being. Our study contributes to the body and knowledge and offers new insights concerning the effects of Coronavirus-19 on the mental condition of international students.